PENDEKATAN PENDIDIKAN NILAJ SECARA KOMPREHENSIF SEBAGAI SUATU ALTERNATIF PEMBENTUKAN AKHLAK BANGSA - Darmiyati Zuchdi Darmiyati Zuchdi (Jurnal Cakrawala Pendidikan, 2001)
The eclining quality of the Indonesian character needs to be resolved. One of the ways tosolve this problem is through the educational practice, by using a more effective approach.A single approach of values education is considered to be ineffective, that is why it isneeded a comprehensive one. The development of students' personality should be holistic innature, including the intellectual, emotional, and spiritual intelligence. Four importantsubstances of values education are values realization, character education, citizenship education,and moral education. Various programs are needed to help young people develop their "lifeskills". The important goals of character education include: respect, responsibility, compassion,self-discipline, loyalty, courage, tolerance, work ethic, and a belief in and love of God. Themajor aspects of citizenship education include: knowledge of being good citizens, appreciationto democratic system and civic values, critical thlnking skills, communication skills, cooperationskills, and conflict resolution skills. The major goal of moral education is to produceautonomous individuals who are in a high level of moral reasoning, are colnlnitted to acting in amanner cosistent with it or who have noble characters.The four important substances stated above are better integrated in Religion Education andPancasila Moral Education. Various strategies of values and moral education should be utilized,including inculcating values, modeling values, facilitating values, and the development of skillsfor achieving a personally peaceful and socially constructive life, as a manifestation of strongfaith.